The price we pay economic and social consequences of inadequate education - Belfield, C. R.; Levin, Henry M.; ProQuest (Firm) (Washington, D.C. : Brookings Institution Press, 2007)
"Highlights costs of inadequate education, attaching hard numbers to the relationship between educational attainment and critical indicators as income, health, crime, dependence on public assistance, and political participation. Explores policy interventions to boost the education system's performance and explains why demographic trends are so challenging to educating the nation's youth"--Provided by publisher.
The education attainment gap : who's affected, how much, and why it matters / Clive R. Belfield and Henry M. Levin -- Assessing the scope of the challenge -- Beyond educational attainment : a multifaceted approach to examining economic inequalities / Richard Rothstein and Tamara Wilder -- Diversity and the demographic dividend : achieving educational equity in an aging white society / Marta Tienda and Sigal Alon -- Implications of educational inequality in a global economy / Thomas Bailey -- Quantifying the costs of inadequate education -- Consequences for the labor market / Cecilia Elena Rouse -- Consequences in health status and costs / Peter Muennig -- Crime and the costs of criminal justice / Enrico Moretti -- Welfare and the costs of public assistance -- Jane Waldfogel, Irwin Garfinkel, and Brendan Kelly -- Directions for reform -- Educational interventions to raise high school graduation rates / Henry M. Levin and Clive R. Belfield -- The promise of early childhood interventions / Clive R. Belfield -- Toward excellence with equity : the role of parenting and transformative school reform / Ronald F. Ferguson -- The need for comprehensive educational equity / Michael A. Rebell.
Includes bibliographical references and index.
Electronic reproduction. Ann Arbor, MI : ProQuest, 2015. Available via World Wide Web. Access may be limited to ProQuest affiliated libraries.
Keywords: Education -- Economic aspects -- United States; Education -- Social aspects -- United States; Education -- United States -- Costs; Educational equalization -- United States; Electronic books